Deflector for XFEL TDS BC1. (September 2016) - Volobuev, E V; Zavadtsev, A A; Zavadtsev, D A; Kravchuk, L V; Paramonov, V V; Sobenin, N P; Churanov, D V
Abstract: Deflector is the part of the Transverse Deflecting System TDS BC1 of the European X-ray Free Electron Laser (XFEL). TDS BC1 is located on the XFEL beam line at the coordinate z=206 m. This system is designed to monitor the longitudinal phase space and the emittance of the accelerated electron bunch after Bunch Compressor 1 (BC1), where electron beam energy is 600 MeV. The deflector includes waveguide window, waveguide load, E-bend, ion pump adapters, two antennas, two ion pumps and 1.7 m long disk-loaded EH-hybrid mode deflecting structure. Operating frequency is 2997.2 MHz. Input RF power is up to 24 MW. The deflector has been manufactured, and all designed RF parameters have been obtained experimentally at low RF power level.